Display structure size affects the production of and response to multimodal duets in magpie-larks. (May 2022) - Ręk, Paweł; Magrath, Robert D.
Abstract : Many group-living animals perform complex and precisely coordinated acoustic and visual displays to signal coalition cohesion or quality. The temporal coordination of such displays is important but matching the type and magnitude of movements may also act as a signal. If so, the relative size of signallers, or signalling structures, could affect their ability to match movements and the perception of matching by receivers. We studied morphology and display in Australian magpie-larks, Grallina cyanoleuca, to assess the importance of wing length and matching of movements during duets that include both movement and song. Partners with more similar wing lengths were less likely to divorce, and in response to audio playback, they were more efficient at cooperative territorial defence. By contrast, dissimilar partners did not produce the movement type that revealed wing lengths. Audiovisual experiments with a robotic pair confirmed that duet displays in which individuals matched their movements were more threatening than those in which the type or magnitude of movement differed. Furthermore, matching by the amplitude of wing movement was more threatening than matching by the angle of motion. Overall, we conclude that movement matching during cooperative duets increases the efficacy of communication and is likely to be enhanced by the similarity in size of signalling structures. Highlights: We studied the importance of wing length and coordination of movement in magpie-larks. We used robotic models to assess the roles of the visual and vocal components. Partners with similar wings were less likely to divorce and cooperated better. When partners matched amplitudes of displays their duets were more threatening. We suggest considering morphological constraints in studies of display coordination.